Granulometrical, mineralogical and geochemical characterization of loess deposits in the Tajo Basin. (2nd July 2016) - Calvo, F.R.; Sánchez, J.; Acosta, A.; Wolf, D.; Faust, D.
Abstract: Loess research has the merit of enabling reconstructions of Pleistocene sedimentation dynamics in many parts of the world. However, there is still very few information regarding the occurrence of loess deposits in the Mediterranean area, even though such records may provide a unique opportunity to investigate landscape evolution for a period for which terrestrial archives are very rare in this region. This paper presents the first results of investigations on a loess sequence in the middle Tajo Valley in central Spain. Findings from detailed granulometrical, mineralogical, geochemical, and grain morphological analyses help to give a first overview on character and composition of these deposits. Very high levels of carbonates (∼60%), but also of gypsum, both to large extents of primary origin, indicate the incorporation of material derived from marls and limestone. Furthermore, we found evidence that allows deduction of possible loess proveniences more precisely. Dolomite contents of up to 20% indicate that the Iberian Range might have been an important source area of loess sediments. The fact that these uplands are located to the east seems to be opposed to the common assumption of prevailing west winds for glacial periods. The studied sequence (Paraiso profile) is one of seven sections that have been investigated as part of a programme to reconstruct Upper Pleistocene landscape dynamics in central Spain. In this context, the detailed characterisation of sediment properties is crucial for discussing loess proveniences and sedimentary environments.